As canções de Francisco Braga: análise estilística e interpretação - Soares, Márcia Aparecida (2015)
This dissertation presents the stylistic analysis of the art songs Prece , Catita , Virgens Mortas , A canção de Romeu and Desejo composed between 1901 and 1910 by Francisco Braga (1868-1945) whose texts are by Brazilian poets in Portuguese language. The analysis of these songs was based on the method proposed by Jan LaRue. We attempted verifying the relationship of these songs to those from the French National Society under the motto Ars Gallica, emphasizing the song from composer Massenet (1842-1912). Based on the results of our analysis we present suggestions for the interpretation of these selected songs.